Improving Structural Adhesion: Experimental and Numerical Analysis of Repair Mortar in Reinforced Concrete - Dursun Bakir; Sedat Savaş; Esra Tuğrul Tunç (Applied Sciences)
The utilization of ecological and cost-effective construction materials has emerged as a critical necessity in contemporary circumstances. It is essential to investigate the use of repair mortar as opposed to epoxy, which offers adhesion to concrete, to guarantee structural integrity under dynamic stresses. In this study, we performed an experimental and computational analysis of the load-bearing capacity of repair mortar to evaluate the adhesion between reinforced concrete structural elements and a geogrid. We performed triaxial bending, compression, splitting, shear bond strength, angle, and adhesion tests on specimens, which were constructed from repair mortar. We constructed 10 × 10 × 50 cm unreinforced beam specimens and 15 × 25 × 200 cm reinforced concrete beams and wrapped the geogrid in the stress zones of the beams by bonding it with repair mortar. We then performed four-point flexural tests on the geogrid specimens wrapped with repair mortar in the tensile zones of these beams. The mechanical properties obtained from these experiments allowed us to create a numerical model. For the first time in the literature, this study investigated the effectiveness of repair mortar compared with epoxy, as well as the innovative use of repair mortar to improve adhesion between the concrete surface and the geogrid. In the literature, reinforcement materials encasing concrete structural elements have utilized epoxy; however, an example of the application of a geogrid wrapped around structural elements with repair mortar has not been previously published. It was concluded that epoxy, effective in adhering to building materials for reinforcement, can bond with structural elements reinforced with a geogrid using repair mortar and may serve as an alternative to epoxy.